GaN Nanopowder synthesis via nitridation: Fabrication and characterization of GaN thin Films for UV detection applications - Mahdi Hajimazdarani; Peyman Yaghoubizadeh; Ali Jafari; Ali Kenarsari Moghadam; Mojtaba Hajimazdarani; Mohammad Javad Eshraghi (Sensors International)
This study presents a novel method for synthesizing gallium nitride nanoparticles via nitridation and their subsequent deposition onto silicon substrates using electron beam evaporation for UV detection applications. The structural and optical properties of the resulting gallium nitride thin films were thoroughly characterized. X-ray diffraction confirmed that the synthesized powder has a wurtzite crystal structure, while the deposited thin film has an amorphous structure. Field emission scanning electron microscopy revealed a uniform layer with an approximate thickness of 150 nm. Energy dispersive spectroscopy confirmed that the stoichiometric ratio of gallium to nitrogen was maintained throughout the coating process. Additionally, ultraviolet diffuse reflectance spectroscopy measurements revealed a bandgap of 3.37 eV for the deposited thin film. Additionally, gold electrodes were deposited on the gallium nitride thin film, and the optical sensor's detection properties were evaluated, demonstrating a sensitivity of 133.6 along with rise and fall times of 18 ms and 15 ms, respectively. These findings underscore the potential of gallium nitride-based materials for advanced optical sensor applications in various fields.